Western red cedar (Thuja plicata) beehives have no impact on honey bee (Apis mellifera) overwintering colony survival or detoxification enzyme expression - Alison McAfee; David R. Tarpy; Leonard J. Foster (PLoS ONE, 2025)
In North America, wooden honey bee hives are most often constructed from pine, but some companies also produce and sell boxes made of western red cedar ( Thuja plicata ) as a result of its local availability and desirable properties. However, there is debate within the beekeeping community about whether cedar is a safe hive material for bees, since resins within the wood are known to be insecticidal or insect deterrents. There is very little empirical evidence to support or refute these arguments. Here, we recorded health metrics of honey bee nucleus colonies hived in western red cedar and pine boxes (n = 10 each) to determine if the type of wood affects colony outcomes. Colonies were produced and introduced into these boxes in late July, with monitoring continued until the following spring. We found no significant differences in adult bee populations, brood areas, or Varroa mite prevalence among colonies hived in cedar versus pine boxes at either the end of summer (September 1st) or spring (April 1st) assessments. Overwintering survival was identical in the two groups at 90%. Hemolymph detoxification enzyme expression differed strongly between callow (day-old) workers and foragers but did not differ with hive material. Overall, we did not find evidence that hiving honey bee colonies in boxes constructed of western red cedar had any negative or positive effect on bee physiology or colony outcomes.